2016
DOI: 10.1186/s12866-016-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Cronobacter identification according to phenotyping methods

Abstract: BackgroundMicrobiological criteria applied to powdered infant formula (PIF) require the absence of all Cronobacter spp. Consequently, misidentification of isolates from finished products can lead to significant financial losses for manufacturers and could increase the risk of neonatal infection. Biochemical identification of suspect isolates using commercially available test panels is recommended for use by PIF manufacturers by both the US FDA and ISO standard methods for Cronobacter species; however, phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
3
18
0
2
Order By: Relevance
“…Methods Together with the fact that Franconibacter and Siccibacter bacteria have biochemical properties very similar to those of Cronobacter bacteria, this all means that it is quite possible that they could be misidentified in the analysis of food or powdered formula samples. In this study, similarly to Jackson et al (29), we too have shown that ID32E misidentifies Franconibacter and Siccibacter strains, predominantly as Cronobacter strains. However, we have also shown that the use of certain biochemical tube tests enables a "pseudo-Cronobacter" strain misidentified by ID32E to be either differentiated from an actual Cronobacter strain or identified as an actual Franconibacter or Siccibacter strain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Methods Together with the fact that Franconibacter and Siccibacter bacteria have biochemical properties very similar to those of Cronobacter bacteria, this all means that it is quite possible that they could be misidentified in the analysis of food or powdered formula samples. In this study, similarly to Jackson et al (29), we too have shown that ID32E misidentifies Franconibacter and Siccibacter strains, predominantly as Cronobacter strains. However, we have also shown that the use of certain biochemical tube tests enables a "pseudo-Cronobacter" strain misidentified by ID32E to be either differentiated from an actual Cronobacter strain or identified as an actual Franconibacter or Siccibacter strain.…”
Section: Discussionsupporting
confidence: 88%
“…However, we have also shown that the use of certain biochemical tube tests enables a "pseudo-Cronobacter" strain misidentified by ID32E to be either differentiated from an actual Cronobacter strain or identified as an actual Franconibacter or Siccibacter strain. All of the above data support Jackson's view that these tests should be replaced by a more reliable identification technique, such as PCR or another molecular biology method (29).…”
Section: Discussionsupporting
confidence: 61%
“…22) . However, they are not always feasible, due to factors such as cost and time 22,23) . Other PCR-based methods are therefore an alternative.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that some Cronobacter isolates were misidentified as Enterobacter or other related species because the API20E and ID32E assays are not fully sensitive for the detection of Cronobacter species [15]. Similarly, sub-culturing isolates with a specific growth medium for pigmentation has also been reported to have a sensitivity of only 80%, and hence sub-culturing was used for further characterisation of the samples but not for isolate selection.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that other samples were missed as Cronobacter species including the two further samples that were API20E positive but ID32E negative. Other Enterobacter species such as E. hormaechei can cause infections from ingested food and have culture profiles similar to those of Cronobacter [15]. Thus, the true burden of Cronobacter disease could be slightly higher, but the plausible number remains very low and it is very unlikely to be a burden of public health significance.…”
Section: Discussionmentioning
confidence: 99%